PENGARUH PENYEIMBANGAN BEBAN TRAFO DISTRIBUSI TERHADAP ARUS NETRAL - Surfa Yondri; Tri Artono; Hengki Purnama Sari (Teknik Elektro Politeknik Negeri Padang, 2013)
Load balancing is load balancing activities in each phase distribution transformers are not balanced, the goal to reduce the magnitude of the neutral current transformer because inequality between phases. This activity was done by measuring each phase transformer load, calculate the average current in each phase, and shifted the burden of heavily loaded phase to phase which has a lot fewer burdens. Load balancing is done on a regular basis every 6 months. PT. PLN (Persero) Rayon Bukittinggi perform load balancing on the distribution transformer substation 100 KVA Distribution Tabek Gadang Tower 2 times on Wednesday, 15th May 2013 at 19:30 pm and Thursday, 16 May 2013 at 19:30 pm. First, by moving the load phase T to phase S at 18 A. Second, by moving the burden from phase to phase R T at 9 A. and load phase T to S phase by 11 A. load balancing distribution transformers 100 KVA Substation Tabek Gadang Tower is near parity with the transformer neutral currents in 14.18 A.